In the footsteps of history: the bees of the genus Hylaeus Fabricius (Hymenoptera, Apoidea: Colletidae) collected by V.I. Roborovsky and P.K. Kozlov in Northwest China (1895–1926) - Proshchalykin, Maxim Yu.; Dathe, Holger H. (Zootaxa, 2018)
An annotated list of 19 species of Hylaeus collected by the famous Russian explorers and travellers V.I. Roborovsky and P.K. Kozlov in Northwest China (1895–1926) is given. Hylaeus (Hylaeus) roborovskyi Proshchalykin & Dathe, sp. nov. is described as new from Xinjiang Uygur Autonomous Region. The following eight known species are newly recorded from China: Hylaeus angustatus (Schenck, 1861), H. arenarius Morawitz, 1876, H. breviceps Morawitz, 1876, H. communis Nylander, 1852, H. fedtschenkoi (Cockerell, 1906), H. pallidicornis Morawitz, 1876, H. pesenkoi Proshchalykin & Dathe, 2016, and H. vulgaris Morawitz, 1876, increasing the number of species reported from the region to 48. New synonymy is established for Hylaeus tsingtauensis (Strand, 1915) = H. montivagus Dathe, 1986, syn. nov.